Preliminary tests of application of RV3 Robot for IMU testing and calibration - Rapinski, Jacek; Smieja, Michal (International Conference “Environmental Engineering”, 2017)
The procedure of calibration of IMU sensors is a very challenging and time consuming task. In order to simplify this process a proposition of an automatic station for IMU calibration is presented in this paper. The use of industrial robot allows for unlimited test trajectory design with high precision reference data. In the article a test stand based on the industrial Mitsubishi RV3 robot is presented. The preliminary test included series of movements of ADIS 16354 6DOF IMU sensor mounted on the robot header. The data gained simultaneously from the IMU sensor and the the robot header trajectory were recorded with the PC. Next, the obtained sets of data in the time domain were translated to the unified coordinates and compared. Finally the differences betwen information comming from both sources were calculated and sensor gyro drift was estimated. The results presented in the the paper show that assumed conception makes it possible to determine the drift of the gyroscope in dynamic conditions.